The Effect of Human Capital Efficiency (HCE), Return on Assets (ROA), Earnings Per Share (EPS), and Debt-to-Equity Ratio (DER) on Market Value Added (MVA) in IDX30 Companies - Reni Arumsari; Rian Andriani; Mochammad Sukrisno Mardiyanto (Journal of Social Research, 2026)
This study aims to analyze the influence of Human Capital Efficiency (HCE), Return on Assets (ROA), Earnings per Share (EPS), and Debt-to-Equity Ratio (DER) on Market Value Added (MVA) in companies listed in the IDX30 index for the period 2020–2024. The phenomenon of negative MVA among large-capitalization companies underscores the importance of integrating financial and non-financial (human capital) performance indicators in corporate valuation. This research employed a quantitative approach using multiple linear regression analysis. The sample was selected using purposive sampling from IDX30 companies that consistently published financial statements throughout the observation period. The results indicate that Return on Assets (ROA) has a positive and significant effect on MVA. Conversely, Human Capital Efficiency (HCE) and Earnings per Share (EPS) have a negative and significant effect on MVA, while Debt-to-Equity Ratio (DER) shows no significant influence. These findings suggest that Indonesian capital market investors respond more favorably to profitability based on operational asset management (ROA) rather than human capital efficiency or the magnitude of earnings per share. The negative results for HCE and EPS signal that high human capital efficiency or earnings per share, if not accompanied by revenue growth, may be perceived negatively by the market. This study implies that management should prioritize operational asset optimization and long-term human capital investment rather than merely pursuing cost efficiency ratios.